In silico exploration of Lycoris alkaloids as potential inhibitors of SARS-CoV-2 main protease (Mpro) - Fredrick Mutie Musila; Grace W Gitau; Magrate M. Kaigongi; Dickson B. Kinyanyi; Jeremiah M. Mulu; Joseph M. Nguta (European Journal of Biological Research, 2022)
Coronavirus disease 2019 (COVID-19) is a pandemic whose adverse effects have been felt all over the world. As of August 2022, reports indicated that over 500 million people in the world had been infected and the number of rising deaths from the disease were slightly above 6.4 million. New variants of the causative agent, SARS-CoV-2 are emanating now and then and some are more efficacious and harder to manage. SARS-CoV-2 main protease (Mpro) has essential functions in viral gene expression and replication through proteolytic cleavage of polyproteins. Search for SARS-CoV-2 Mpro inhibitors is a vital step in the treatment and management of COVID-19. In this study, we investigated whether alkaloids with antiviral and myriad other bioactivities from the genus Lycoris can act as SARS-CoV-2 Mpro inhibitors. We conducted a computer-aided drug design study through screening optimal ligands for SARS-CoV-2 Mpro from a list of over 150 Lycoris alkaloids created from online databases such as ChEMBL, PubChem, ChemSpider, and published journal papers. The In silico study involved molecular docking of Lycoris alkaloids to SARS-CoV-2 Mpro active site, absorption, distribution, metabolism, elimination and toxicity (ADMET) screening and finally molecular dynamic (MD) simulations of the most promising ligand-SARS-CoV-2 Mpro complexes. The study identified 3,11-dimethoxy-lycoramine, narwedine, O-demethyllycoramine and epilycoramine as drug-like and lead-like Lycoris alkaloids with favorable ADMET properties and are very likely to have an inhibition activity on SARS-CoV-2 Mpro and may become potential drug candidates.